Cow’s microbiome from antepartum to postpartum: A long-term study covering two physiological challenges - Tröscher-Mußotter, Johanna; Deusch, Simon; Borda-Molina, Daniel; Frahm, Jana; Dänicke, Sven; Camarinha-Silva, Amélia; Huber, Korinna; Seifert, Jana (Frontiers in Microbiology, 2022)
Little is known about the interplay between the ruminant microbiome and the host during challenging events. This long-term study investigated the ruminal and duodenal microbiome and metabolites during calving as an individual challenge and an LPS induced systemic inflammation as a standardized challenge. Strong inter- and intra-individual microbiome changes were noted during the entire trial period of 168 days and between the 12 sampling time points. Bifidobacterium increased significantly at three days after calving. Both challenges increased the intestinal abundance of fiber associated taxa, e.g., Butyrivibrio and unclassified Ruminococcaceae. NMR analyses of rumen and duodenum samples identified up to 60 metabolites out of which fatty and amino acids, amines, and urea varied in concentrations triggered by the two challenges. Correlation analyses between these parameters indicated a close connection and dependency of the microbiome with its host. It turns out that the combination of phylogenetic with metabolite information supports the understanding of the true scenario in the forestomach system. The individual stages of the production cycle in dairy cows reveal specific criteria for the interaction pattern between microbial functions and host responses.